2016
DOI: 10.1186/s13104-015-1768-6
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy in Denmark 1980–2010: a review of 15 cases

Abstract: BackgroundLeprosy, caused by Mycobacterium leprae, is a chronic and progressive granulomatous disease affecting mainly the skin and the peripheral nervous system. If left unrecognized, the infection can lead to permanent nerve damage and disability. The clinical presentation depends on the immune response of the patient and can result in a wide spectrum of symptoms. Leprosy is a rare encounter in Scandinavia but remains endemic in some parts of the world, with some areas reporting an increasing incidence. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…Nineteen papers published between 2009 and 2018 were included in the review, accounting for 280 patients reported by five nationwide reports [ 7 , 8 , 9 , 22 , 23 ] ( Table 2 ), 14 case reports [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], and three case series described by single centers [ 7 , 38 , 39 ] ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen papers published between 2009 and 2018 were included in the review, accounting for 280 patients reported by five nationwide reports [ 7 , 8 , 9 , 22 , 23 ] ( Table 2 ), 14 case reports [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], and three case series described by single centers [ 7 , 38 , 39 ] ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Europe, leprosy incidence declined after the late medieval period with no cases reported to the WHO during the period 2009–2014, followed by an increased detection trend from 18 cases during 2015 to 50 cases at the end of 2018 [ 6 ], prevalently in foreign-born patients [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…One Mycobacterium leprae infection was acquired in the Comoros. A French study conducted from 2009 to 2013 reported that the Comoros were the main focus of Mycobacterium leprae infections diagnosed in France [24], while in a study conducted in Madrid, from 1989 to 2015, most cases were migrants from South America [25] and in a Danish study conducted from 1980 to 2010, most cases were migrants from South-East Asia [26]. In our study, one Bartonella henselae case was diagnosed in a patient returning from Morocco, a disease rarely described in Morocco [27][28][29][30], while fleas have been shown to be positive for Bartonella henselae in this country [31].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoesthesia skin lesion is the most important diagnostic factor because it is not expected in another skin disease other than leprosy. After evaluation of skin lesions, peripheral nerves should be palpated for thickening, and nerve examination of lesions and distal extremities should be performed [69]. Conjunctiva and corneal examination should also be made.…”
Section: Diagnosismentioning
confidence: 99%
“…1000 bacillus in every area) with the amount of bacteria in each microscope area. Patients with BI scores lower than 2 are considered as PB, whereas BI scores above 2 are considered MB [69].…”
Section: Microscopic Examinationmentioning
confidence: 99%